The Effect of Supervision on ASN Performance Based on the E-SIKAP Application in Public Elementary Schools Throughout Batang Anai District - Algeri, Dea Fazana; Ningrum, Tia Ayu; Hadiyanto; Setiawati, Merika (Journal of Practice Learning and Educational Development, 2026)
Teacher performance as State Civil Apparatus (ASN) plays an important role in improving the quality of education. However, the implementation of the E-SIKAP application in elementary schools still faces several problems, such as delays in reporting, inconsistency in task implementation, and suboptimal supervision. Therefore, this study aimed to determine the effect of supervision on ASN performance through the E-SIKAP application in public elementary schools throughout Batang Anai District. This study employed a quantitative approach with a correlational method. The population consisted of ASN working in public elementary schools, with 168 respondents selected using proportional random sampling. Data were collected through validated and reliable questionnaires and analyzed using descriptive statistics, normality tests, linearity tests, simple linear regression, t-tests, and coefficient of determination tests using SPSS 31 for Windows. The findings showed that supervision was categorized as very good, with a Total Respondent Achievement Level (TCR) of 91.21%, while ASN performance through the E-SIKAP application was also categorized as very good. Hypothesis testing indicated that supervision had a significant effect on ASN performance, with a significance value of <0.001. The coefficient of determination (R²) was 0.922, indicating that supervision contributed 92.2% to ASN performance. The study concludes that effective and technology-based supervision can improve ASN discipline, responsibility, and work accountability. Therefore, school principals are expected to strengthen supervision and optimize the implementation of E-SIKAP to improve ASN performance in elementary schools.